Penerapan Model Pembelajaran Snowball Throwing Untuk Meningkatkan Prestasi Belajar Siswa Kelas V SDN Ngiliran I Kecamatan Panekan Kabupaten Magetan Materi Daur Air (Eduscotech, 2024)
Science learning in elementary schools often faces challenges in improving students' learning achievement and active involvement, especially in materials that require a deep understanding of scientific concepts such as the water cycle. This study aims to test the effect of implementing the Snowball Throwing learning model on improving students' learning achievement and involvement in the water cycle material in grade V of SDN Ngiliran I, Panekan District. This study used a pretest-posttest experimental design with a sample of 30 students, where data were collected through learning outcome tests, observations, and involvement questionnaires. The results showed a significant increase in posttest scores compared to pretests, as well as an increase in student involvement in group discussions and collaborations. This study provides evidence that the Snowball Throwing model can improve students' learning achievement and active involvement in science learning, and suggests the use of this model in other materials to improve the quality of learning. Suggestions for further research are to test the application of this model in other materials and use a larger sample to confirm these findings.